International survey on the impact of parasitic infections: frequency of transmission and current mitigation strategies. Issue 1 (6th December 2018) - Leiby, David A.; O'Brien, Sheila F.; Wendel, Silvano; Nguyen, Megan L.; Delage, Gilles; Devare, Sushil G.; Hardiman, Anthony; Nakhasi, Hira L.; Sauleda, Silvia; Bloch, Evan M.; ,
Abstract : Background and Objectives: Globally, blood safety interventions have been successful in mitigating risk of the major transfusion‐transmitted (TT) viruses. However, strategies that address risk from parasites are comparatively limited. TT parasites are often regional in nature, posing unique challenges; we sought to understand their impact on blood safety. Materials and Methods: An electronic questionnaire was distributed to transfusion medicine leaders in 100 countries. The survey focused on specific questions pertaining to four parasitic diseases: babesiosis, Chagas, leishmaniasis and malaria. Respondents provided data on historical TT cases, local epidemiology, policies to mitigate risk and an assessment of public health perceptions for each aetiologic agent. Results: Twenty‐eight (28%) surveys were returned from countries in Europe ( n  = 13), the Americas ( n  = 6), Africa ( n  = 4), Asia ( n  = 3) and Oceana ( n  = 2). Historically, no cases of TT leishmaniasis were reported, TT babesiosis was exclusive to Canada and the USA, TT Chagas was limited to the Americas and Spain, while TT malaria was cosmopolitan. Mitigation efforts varied widely; malaria was the most frequently tested parasitic disease. The public's perception of risk for parasitic agents was low, while that of health authorities in endemic countries was higher. Conclusion: The global impact of parasitic infections on blood safety and related mitigation efforts varied widely by parasite epidemiology, test availability, public health priorities and socioeconomic constraints. While parasites continue to pose a risk to blood safety, the successful mitigation of viral risk has elevated the prominence of TT parasites in many locations, thereby requiring consideration of mitigation efforts.